G102(P) Taking a Breather: Refining a Method of Inducing Hypoxia. (7th April 2014) - Wilson, J; Dyamond, T; Rutter, M; Ross Russell, R
Abstract : Introduction: We have previously shown that it is possible to derive pulmonary shunt and ventilation/perfusion (VQ) ratios from measurements of partial pressure of inspired oxygen (PIO2) and oxygen saturation (SpO2 ) data on SpO2 levels below 90%. In order to do this in healthy patients it is necessary to make them hypoxic by dropping their PIO2 below air levels of 21%. Aims: We wanted to assess the reliability and reproducibility of using nitrogen given through a Venturi device (entraining room air) into a mask to deliver a consistent hypoxic gas mix. Methods: Pure nitrogen was delivered through a number of Venturi devices and the rate of flow of nitrogen was varied between 2l/min and 15l/min. The mask was placed over the face of a dummy and an oxygen probe was placed inside the mask to measure the percentage of oxygen. Ten measurements were made for each data point. We also assessed the impact of tidal flow on gas delivery, using a one litre syringe to mimic breathing during the measurements. Results: Delivering nitrogen through a Venturi device to entrain air gives consistently uniform oxygen concentrations delivered to the mask. Flows through the five different Venturi devices delivered 20.0%, 18.5%, 16.2%, 15.3% and 10.5% PIO2 respectively. Flows between 2l/min and 15l/min caused a variability in PIO2 of less than 0.5% for each device tested. When mimicking tidal breathing, we could demonstrate variability in delivered PIO2, caused by entrainment of air around the mask. To counteract this, several different designs were evaluated to provide a gas reservoir but this proved technically difficult, as the increased resistance affected air entrainment and PIO2 . Conclusion: Using a flow of nitrogen through a Venturi device connected directly to a mask is a consistent and flow independent method of delivering low oxygen concentrations. The effect of tidal breathing on delivered PIO2 needs to be assessed further. Reference: Sapsford D, Jones JG. Eur J Anaesthesiol 1995;12:375